The Effect of Red Spinach Pudding on Increasing Haemoglobin Levels in Adolescent Girls - Siti Fatimah; Alfira Fitriana; Nurul Khoirun Nisa; Achmad Fauzi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Anemia is one of the major global he alth problems and a primary conce rn in developing countries, particularly in Indonesia. An estimated one-third of the world’s population experiences anemia, with adolescent girls representing one of the most vulnerable group. One non-pharmacological way to treat anemia is by increasing the intake of foods high in iron, such as red spinach. Red spinach (Amaranthus tricolor L.) contains iron, vitamin C, and antioxidants that play a role in increasing hemoglobin formation. This study aims to analyze the effect of red spinach pudding on increasing hemoglobin levels among adolescent girls. This research employed a quasi-experimental design with a one-group pretest–posttest. The sample consisted of 26 respondents selected total sampling technique, normal data was obtained that used the paired simple t-test analysis. The results showed a highly significant difference between hemoglobin levels before and after the administration of red spinach pudding, with p value = 0.000 (< 0.05), a mean difference of 1.42, and a Standard Deviation (SD) difference of 0.69. The study findings that red spinach pudding effectively increases hemoglobin levels among adolescent girls and may serve as a promising nutritional intervention for the prevention and management of anemia in this population